Innovative Approaches to Public Services Delivery through the Prism of the Industry 5.0 Paradigm. - Bokayev, Baurzhan; Amirova, Aigerim; Abilzhan, Galy; Yessengeldina, Anar; Sadykova, Kuralay (Innovation Journal, 2024)
The article analyzes case studies based on innovative approaches to the delivery of public services in Kazakhstan emerging from and interpreted through the Industry 5.0 Paradigm. These approaches are defined by a common desire to provide services that are consciously and proactively human and citizen -entered. The Industry 5.0 Paradigm is a new stage of industrialization characterized by citizen-centricity principle and advanced technology implementation. Its impact is growing, with researchers and public officials paying increasing attention to the parameters of implementation. However, analysis of the application of these approaches through digital portals, shows that a number of omissions currently prevent public services delivery from reaching their full potential. The same perspective on difficulties associated with e-services provision was received from survey results. From January till November 2023 about 52,612 questionnaires for 373 electronic public services were distributed among all 20 regions of Kazakhstan. Besides this, 9,954 respondents have assessed the overall quality of public services delivery based on several criteria. The "Feedback" indicator had the lowest estimated average score and level of satisfaction. The analysis of quality of public services delivery shows that starting in 2020 there is an upward trend associated with the proactive digitization in Kazakhstan. The study provides several suggestions on this issue for policy decision makers, as well as for relevant government bodies and for future research.